MENGANALISIS TERJEMAHAN DAN NILAI-NILAI PENDIDIKAN DALAM SURAH AL-WAQI’AH - Erma Muti'ah; Nurul Hidayah (LPPM Universitas KH. A. Wahab Hasbullah, 2020)
Al-Qur'an is a holy book that was revealed by Allah SWT to Prophet Muhammad SAW through the intermediary of the angel Gabriel. The Qur'an is also a holy book that records all events in the universe, both present, past and future events that occur in humans. The content in the Qur'an also discusses the Day of Judgment and the place of humans eternally in the hereafter. One of the contents of the Qur'an which discusses the Day of Judgment is stated in the Surah Al-Waqi'ah. In the Qur'an there are many educational values, including in the Surah Al-Waqi'ah. The value of education is something that is valuable for humans, because the value of education includes the value of moral education and religious values, so that it is concluded in the purpose of education, namely to foster one's personality for provisions in the hereafter. This research is library research using descriptive analysis method and aims to describe the semantic analysis of the translation of Surah Al-Waqi'ah. To decipher the letter Al-Waqi'ah. To describe the letter Al-Waqi'ah, the author only focuses on two interpretations, namely: Quraish Shihab, Tafsir Al-Mishbah, and the Ministry of RI, Al-Qur'an and its interpretation.